Website-Based Patient Complaint Information System at Hidayah General Hospital, Boyolali - I Made Selamet Sudiana; Nurhayati; Agung Suryadi (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
Background:Patient complaints at Hidayah General Hospital, Boyolali, are still handled through direct submissions, WhatsApp, and Google Reviews, which poses a risk of data loss and difficulty in monitoring follow-up. Objective: This study aims to build a website-based patient complaint information system. Method: The study used a descriptive method with a cross-sectional approach. The subjects were Public Relations and Training officers. The instruments were observation and interview guidelines, while data collection was carried out through observation, interviews, and document review. Data were analyzed descriptively. The system was developed using the Systems Development Life Cycle with the Waterfall model. Result: The system provides complaint submission features, automatic complaint tickets, status tracking, responses and follow-ups, satisfaction surveys, statistics, and report printing. Conclusion: The developed system supports more structured patient complaint management and facilitates monitoring of complaint follow-up, thereby supporting hospital service management.